2014
DOI: 10.1108/prt-09-2013-0079
|View full text |Cite
|
Sign up to set email alerts
|

Effect of polyvinylpyrrolidone – polyethylene glycol blends on the corrosion inhibition of aluminium in HCl solution

Abstract: Purpose – The purpose of this paper is to investigate the effect of polyethylene glycol (PEG), polyvinylpyrrolidone (PVP) and blended formulations on the corrosion inhibition of aluminium in HCl solutions at 30-60°C and to study the mechanism of action. Design/methodology/approach – The inhibitive effect of the homopolymers and polymer blend was assessed using weight loss and hydrogen evolution methods at 30 and 60°C. The morphology of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 49 publications
(53 reference statements)
0
9
0
Order By: Relevance
“…In literature studies, synergism between organic inhibitors and halide ions against corrosion of metal in acidic solution has been investigated [15][16][17][18]. The synergistic inhibition effect of combinations of two polymers has been presented in literature; For instance, Umoren [19] and Umoren et al [20] reported a synergistic effect of polyethylene glycol-polyvinyl pyrrolidone blends for inhibition of corrosion of mild steel and aluminum in acidic solution. The results suggested that the mixture could find practical applications for corrosion control in acidic aqueous environments.…”
Section: Introductionmentioning
confidence: 96%
“…In literature studies, synergism between organic inhibitors and halide ions against corrosion of metal in acidic solution has been investigated [15][16][17][18]. The synergistic inhibition effect of combinations of two polymers has been presented in literature; For instance, Umoren [19] and Umoren et al [20] reported a synergistic effect of polyethylene glycol-polyvinyl pyrrolidone blends for inhibition of corrosion of mild steel and aluminum in acidic solution. The results suggested that the mixture could find practical applications for corrosion control in acidic aqueous environments.…”
Section: Introductionmentioning
confidence: 96%
“…DS * values are all negative which implies that the activated complex in the rate-determining step represents an association rather than dissolution, meaning that a decrease in degree of disorderliness of the system takes place on moving from reactants to activated complex [7,53]. The positive sign of DH * reflects the endothermic nature of mild steel corrosion in 0.5 M H 2 SO 4 solution [54].…”
Section: Effect Of Temperaturementioning
confidence: 95%
“…Inorganic (particularly chromates, dichromates, nitrites, nitrates, phosphates, etc.) and organic (mostly those with O, N, S, and P atoms and/or p electrons) compounds have been effective in this regard [5][6][7] but the toxic nature of most inorganic compounds to the natural ecosystem and the exorbitant prices in addition to the tedious synthetic route of organic compounds have been very worrisome. Polymers, both naturally occurring and synthetic had been tested for metal corrosion inhibition ability [8,9] so as to serve as replacement for the inorganic and organic corrosion inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…Umoren et al 106 tested polyethylene glycol (PEG) and PVP as well as their mixtures as corrosion inhibitors for 3SR (98.60% aluminium) aluminium alloy in 0.1 M HCl solution at 30-60 °C, using the WL and HE techniques. The inhibition effectiveness of the single compounds increased with increasing compound concentration, but decreased with increasing temperature.…”
Section: Organic Corrosion Inhibitors In Hcl Solutionmentioning
confidence: 99%